Optimum design of two-material bending plate compliant devices. Issue 1 (12th October 2021) - Romero, Augusto
Abstract : Purpose: The purpose of this study is to explore the optimum design of bending plate compliant mechanisms subjected to pure mechanical excitations using topological-derivative-based topology optimization. The main objective is to design the reinforcement in a plate of base material. Design/methodology/approach: The optimum design is performed by means of a level-set representation method guided by topological derivatives. Kirchhoff and Reissner–Mindlin models are used to solve the linear bending plate problem. A qualitative comparison has been carried out between the optimal obtained topologies for each model. Findings: The proposed methodology was able to design reinforcement in a plate of the base material. The obtained reinforcements notably improve the device's behavior. The shape and topology of the reinforcements vary depending on the mechanical plate model considered. In fact, in the Reissner–Mindlin solutions, very thin flexo-torsional hinges connecting big zones of the reinforcement material are designed. Originality/value: Up to date, the synthesis of ortho-planar mechanisms by means of continuum topology optimization was only boarded within a multi-physics context. In this work, the optimal design of pure ortho-planar compliance actuators is addressed. The best performance is found by analyzing the results for two classical mechanical plate models.